Implementing integrated business planning : a guide exemplified with process context and SAP IBP use cases /: a guide exemplified with process context and SAP IBP use cases. ([2019]) - Kepczynski, Robert; Dimofte, Alecsandra; Jandhyala, Raghav; Sankaran, Ganesh
No abstract available